2021
DOI: 10.3389/fneur.2020.610163
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs as Promising Diagnostic Biomarkers for Patients With Glioma: A Meta-Analysis

Abstract: Backgrounds and Purpose: Currently, circulating microRNAs (miRNAs) are considered to be non-invasive diagnostic biomarkers in a broad range of tumors. Nevertheless, so far, miRNAs have not been fully applied to the clinic for routine screening in glioma patients. Thus, our goal is to evaluate the diagnostic performance of circulating miRNAs for gliomas via a meta-analysis. The present study is registered on the PROSPERO website, with the number CRD42020195883.Methods: Literature retrieval was implemented in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…We know that stable miRNA expression is measurable from bodily fluids such as cerebrospinal fluid or blood serum [ 20 , 21 ] but that specific miRNAs in the diagnosis of a glioma, in particular at the early stage, are still missing [ 22 ]. We thus next tested the possibility of directly assaying the microRNAs studied in this study from the patient’s blood sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We know that stable miRNA expression is measurable from bodily fluids such as cerebrospinal fluid or blood serum [ 20 , 21 ] but that specific miRNAs in the diagnosis of a glioma, in particular at the early stage, are still missing [ 22 ]. We thus next tested the possibility of directly assaying the microRNAs studied in this study from the patient’s blood sample.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, miRNAs have not yet come to be used in daily clinical practice. To relaunch the debate on their possible clinical interest, particularly for the diagnosis of patients with gliomas, a meta-analysis recently tested the diagnostic performance of circulating miRNAs for gliomas [ 22 ]. After analyzing 18 articles covering 24 studies containing 2170 glioma patients and 1456 healthy participants, the authors concluded that circulating miRNAs have the potential to serve as diagnostic biomarkers for gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are few biomarkers allowing early detection of gliomas. Several studies using multiparametric MRI texture analysis, 86 circulating biomarkers, 87 or micro RNAs 88 have shown their usefulness as biomarkers for patients with glioma. Maleschlijski et al 74 have also described a strategy for metabolic profiling of glioma subtypes from ex vivo HR-MAS spectra.…”
Section: Biomarker Analysismentioning
confidence: 99%